A new troglomorphic Metagonia Simon 1893 (Araneae, Pholcidae) from Brazil - Machado, Ewerton O.; Ferreira, Rodrigo L.; Brescovit, Antonio D. (Zootaxa, 2011)
The genus Metagonia Simon 1893 currently has 81 species widely distributed in South and Central America (Platnick, 2011). The majority of species are leaf-dwellers (Gertsch 1986; Huber 1997; 2004; Huber & Schütte 2009) but some inhabit leaf-litter (Huber et al. 2005) or live in caves (Gertsch 1986; Gertsch & Peck 1992; Huber 1998; Pérez González & Huber 1999). Three species were described from cave environments as eyeless troglobites: M. bellavista Gertsch & Peck 1992 and M. reederi Gertsch & Peck 1992 from the Galapagos Islands and M. debrasi Pérez González & Huber 1999 from Cuba. These species may be local relicts from extinct groups (Gertsch & Peck 1992, Pérez González & Huber 1999). Huber (2000) placed these eyeless species in his ‘group 4’.